Some Suggestions to Defend Viva-voce Successfully - Pokharel, Samidha Dhungel (PRAGYAN A Peer Reviewed Multidisciplinary Journal, 2021)
Viva voce, the oral presentation of academic research, also known as thesis defense, is nerve wracking experience for most of the students. Many experienced people also become panic during paper presentation in front of scholars. In such context, it would not be a surprise if students become nervous during their thesis defense. The objective of this paper is to explore the experiences of the scholars during viva voce and make students informed about the steps to prepare oral presentation. This study is based on primary and secondary data. Four case studies were collected from PhD holders from Universities of Nepal through personal communication during the year 2016. Secondary data were pulled from web sites. The findings of the study revealed that many of the scholars including national and international have unpleasant experiences. Such unpleasant experiences are not associated with only students’ poor work, poor presentation, and nervousness but also with committee members’ attitude, and unclear questions. It can be concluded that the work of the students’ is already evaluated and recommended to award degree by the supervisor, co-supervisor, and internal examiner. Therefore, it can be said that the viva voce should not be only one determining factor for assessing whether to award degree or not. However, it is students’ responsibility to defense their viva perfectly.